Price dividend ratio and long-run stock returns: A score driven state space model - Davide Delle Monache; Ivan Petrella; Fabrizio Venditti (European Central Bank (ECB), 2020)
In this paper we develop a general framework to analyze state space models with timevarying system matrices where time variation is driven by the score of the conditional likelihood. We derive a new filter that allows for the simultaneous estimation of the state vector and of the time-varying parameters. We use this method to study the timevarying relationship between the price dividend ratio, expected stock returns and expected dividend growth in the US since 1880. We find a significant increase in the long-run equilibrium value of the price dividend ratio over time, associated with a fall in the longrun expected rate of return on stocks. The latter can be attributed mainly to a decrease in the natural rate of interest, as the long-run risk premium has only slightly fallen.
Keywords: C22; C32; C51; C53; E31; 330; State space models; time-varying parameters; score-driven models; equitypremium; present-value models